2015
DOI: 10.1242/dmm.018127
|View full text |Cite
|
Sign up to set email alerts
|

Increased autophagy and apoptosis contribute to muscle atrophy in a myotonic dystrophy type 1 Drosophila model

Abstract: Muscle mass wasting is one of the most debilitating symptoms of myotonic dystrophy type 1 (DM1) disease, ultimately leading to immobility, respiratory defects, dysarthria, dysphagia and death in advanced stages of the disease. In order to study the molecular mechanisms leading to the degenerative loss of adult muscle tissue in DM1, we generated an inducible Drosophila model of expanded CTG trinucleotide repeat toxicity that resembles an adult-onset form of the disease. Heat-shock induced expression of 480 CUG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 60 publications
19
81
0
Order By: Relevance
“…Firstly, administration of recombinant Mbnl1 protein to a HSA LR mouse model of DM1, rescues myotonia and the splicing alterations characteristic of DM126. Secondly, we showed that the overexpression of a muscleblind isoform partially rescues muscle atrophy in a Drosophila DM1 model27. Finally, MBNL1 overexpression is well tolerated in skeletal muscle in transgenic mice where it causes only relatively minor splicing changes but no effect on longevity28.…”
mentioning
confidence: 75%
“…Firstly, administration of recombinant Mbnl1 protein to a HSA LR mouse model of DM1, rescues myotonia and the splicing alterations characteristic of DM126. Secondly, we showed that the overexpression of a muscleblind isoform partially rescues muscle atrophy in a Drosophila DM1 model27. Finally, MBNL1 overexpression is well tolerated in skeletal muscle in transgenic mice where it causes only relatively minor splicing changes but no effect on longevity28.…”
mentioning
confidence: 75%
“…The involvement of autophagy in DM1 was largely deduced from the presence of autophagic vesicles and/or accumulation of autophagic markers in DM1 cells, but usually without dynamic measurement of the autophagic flux (13,14,17,19,36,37,49). In our study, we combined several methods to establish that mild changes in autophagic markers in muscle from HSA LR mice are caused by autophagic flux limitation during the degradation steps.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, deregulation of cellular processes and signaling pathways important for maintaining proper muscle homeostasis has been reported in DM1. This includes abnormal activation of the ubiquitin-proteasome system and increased autophagic flux, which were both related to muscle atrophy and weakness in DM1 (12)(13)(14). In parallel, perturbation in the PKB/Akt pathway may arise from altered expression of the insulin receptor, which correlates with glucose intolerance in DM1 patients (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to autophagy, EPO inhibits autophagy through the activation of mTOR (20, 57, 266). Activation of mTOR blocks autophagy by phosphorylating autophagic related genes ( Atg ) and proteins that include Atg13 and ULKs to inhibit the UNC like kinase complex ULK-Atg13-FIP200 (37).…”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%